Historia Zakładu Publicznego Prawa Gospodarczego w Instytucie Nauk Administracyjnych Wydziału Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego - Horubski, Krzysztof; Małecki, Witold (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The history of the Division of Public Economic Law dates back to 1973, when it was established within the structure of the Institute of Administrative Sciences, under the name of the Divition of National Economy Administration. Despite the transformation of the economic system, the main areas of scientific research and teaching assignments remain to be: state influence on economic processes, the principle of freedom of economic activity and its limits, public property management. The heads of the Division — Prof. Adam Chełmoński and Prof. Leon Kieres — not only belong to the most outstanding figures among Polish administrative law scholars, but have also stood out in public service activities. Over the years the staff of the Division has attained remarkable achievements in both scientific and didactic work. Scientific achievements include, among others, a significant contribution to the preparation of a fundamental work Public Economic Law, published in the series “System of Administrative Law”. The didactic work is carried out by the staff and doctoral students of the Division in all courses of study conducted by the Faculty of Law, Administration and Economics. The Division is among the most frequently chosen units for preparation of bachelor, master and doctoral theses by the students of the Faculty.
Keywords: Zakład Publicznego Prawa Gospodarczego; Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego; historia